Promoting the emotional well-being of children and adolescents and preventing their mental ill health : a handbook - Dwivedi, Kedar Nath; Harper, Peter Brinley, 1955- (J. Kingsley Publishers, 2004)
This comprehensive guide provides overviews of the key psychological processes affecting mental health, such as development, attachment, emotion regulation and attention, and draws out the implications for preventive measures and promotion of emotional well-being. The authors, from a range of professional disciplines, emphasise the importance of early intervention and prevention, exploring in particular how initiatives in parenting and education can promote children's emotional well-being. The topics they cover include: the prevention and management of addiction and eating disorders; the devel.